Progressão da dificuldade técnica nas três suítes brasileiras para piano de Oscar Lorenzo Fernândez - Junia Goncalves Santiago (2007)
This study focuses on the investigation of a progression of technical difficulty throughout the three Suítes Brasileiras for solo piano, by Oscar Lorenzo Fernândez (1897 1948), departing from its writing and piano technique, using tools that help to identify the existing difficulties. An analysis of the work was made through the use of the following pre-determined categories: tempo and rhythm, melody, texture andsonority. To each one of these categories three possible levels of difficulty were given: low difficulty, reasonable difficulty, much difficulty. This analysis, produced in a quantitative and qualitative way, established comparisons between the pieces and confirmed, through the criteria used, the existence of a gradation of pianistic difficultyin the three Suítes Brasileiras.